Taxonomy and phylogeny of Pseudovorticella ciliates (Ciliophora, Peritrichia): Two new and one rare species from the coastal waters of China - Zhang, Yong; Yu, Ying; Qu, Zhishuai; Jiang, Mengmeng; Shen, Zhuo; Li, Jiqiu; Lin, Xiaofeng (Frontiers in Marine Science, 2022)
Peritrich ciliates are a species-rich group of sessile unicellular eukaryotes, which can be found in various aquatic habitats from all over the world. It is well accepted that there are still many ciliates to be uncovered. During a survey on ciliate biodiversity in coastal waters of China, three solitary peritrich species were identified as members of the genus Pseudovorticella Foissner & Schiffmann, 1975, including two new species and a rare one. Pseudovorticella zhejiangensis sp. n. differs from its congeners mainly having a conical shaped zooid, conspicuous pellicular blisters, one ventral and one dorsal contractile vacuoles, and an infundibular polykinety 3 with three rows of equal-length. Pseudovorticella dalianensis sp. n. can be defined mainly by an obovoid shaped zooid, one ventral contractile vacuole and a three-rowed infundibular polykinety 3 with the middle row being the longest. The rare species, P. verrucosa (Dons, 1915) Sun et al., 2009 was redescribed and its neotype was assigned. The small sub-unit (SSU) rDNA sequences of these three species were sequenced for the first time and the phylogeny of Pseudovorticella species was analyzed. The results verified the non-monophyly of this genus. Moreover, considering their phylogenetic relationships and genetic distances among Pseudovorticella species, two undefined Pseudovorticella isolates with sequence accession numbers MW046187 and MW046188 were suggested to be populations of P. zhejiangensis sp. n. This study demonstrates that the morphologic and gene barcoding data are the optimum combination to disclose ciliates biodiversity.